2016
DOI: 10.1111/jsr.12414
|View full text |Cite
|
Sign up to set email alerts
|

Development of infant and toddler sleep patterns: real‐world data from a mobile application

Abstract: The aim of this study was to investigate the development of infant and toddler sleep patterns. Data were collected on 841 children (aged from birth to 36 months) via a free, publicly available, commercially sponsored iPhone app. Analyses were conducted on caregiver recordings of 156 989 sleep sessions across a 19-month period. Detailed visualizations of the development of sleep across the first 3 years of life are presented. In the first 3 months, sleep sessions primarily lasted less than 3.5 h throughout the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 23 publications
5
44
1
4
Order By: Relevance
“…Chang et al Reported a negative correlation between sleep latency and sleep duration and daily nap time, which is in contradiction with the results of the present study [32]. Also, the inverse correlation of sleep duration with toddler age is similar to the results of other studies [29][30][31][32][33]. As expected, sleep duration will naturally decrease with age [8].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Chang et al Reported a negative correlation between sleep latency and sleep duration and daily nap time, which is in contradiction with the results of the present study [32]. Also, the inverse correlation of sleep duration with toddler age is similar to the results of other studies [29][30][31][32][33]. As expected, sleep duration will naturally decrease with age [8].…”
Section: Discussioncontrasting
confidence: 99%
“…The mean age of the fathers was 34.8±5.1 years and 10.18% were college educated. 33 were younger than 24 months and 21 were older than 24 months; ** Of the 66 boys in the study, 39 were younger than 24 months and 27 were older than 24 months; *** Significant at P <0.001. the strongest correlation coefficients were between sleep duration and sleep anxiety (r = -0.527), sleep duration and resistance to sleep (r = 0.473), sleep place and resistance to sleep (r = -0.471) (P <0.001), respectively. Table 3 presents standard and non-standard regression coefficients between demographic variables and CSHQ questionnaire subscales in toddlers participating in the study.…”
Section: Participant Characteristicsmentioning
confidence: 98%
“…Average sleep duration was not significantly different on weekdays compared with weekend days 9.93 (SD = 0.86) vs 10.06 (SD = 0.91), .20, and thus was examined as a single variable across all nights for subsequent analyses. Bed and wake times were statistically different on weekdays compared with weekend days, with a delay of 35 minutes in bedtime and 9 minutes in wake time on weekends compared with weekdays (both P < .05); however, given the small magnitude of difference and because some degree of variation in sleep timing is expected, sleep times were also examined as single variables across all nights for analyses. Pairwise Pearson correlations showed that wake time was positively correlated with sleep duration ( r = .47) and bedtime ( r = .62) and bedtime was inversely correlated with sleep duration ( r = −.25).…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative description of these temporal patterns requires large data sets which, in turn, requires the willingness of many parents to record the sleep of their offspring, preferably during a long period of time. Mobile phone applications may be a good way to entice parents to do so, and in the second paper on paediatric sleep in this issue the potential of this approach is illustrated convincingly (Mindell et al ., ). Although many of the phenomena described in this paper are well known, e.g.…”
Section: Mobile Phone Application As a Tool To Study The Development mentioning
confidence: 97%